Understanding Tax Policy Research in Indonesia: A Bibliometric Perspective - Perdana, Gusti Naufal Rizky; Haliza, Elza Fatika Nur (Journal of Applied Sciences in Accounting, Finance, and Tax, 2024)
This study aims to conduct a bibliometric analysis of tax policy in Indonesia, focusing on identifying research trends, dominant issues, and emerging research themes in this field. Data obtained from the Scopus database using the keywords "tax policy" and "Indonesia" were analyzed using bibliometric methods to depict the structure and research trends, while thematic approaches were employed to identify dominant themes. The results indicate a steady increase in the number of publications on tax policy in Indonesia, particularly in the last five years. Specifically, in 2020 there will be 8 documents, in 2022 there will be 9 documents and in 2023 there will be 18 documents. The analysis also identifies the authors, affiliations, and countries that contribute most to this research, as well as the most common document types and subject areas. The most frequently cited articles in the context of tax policy in Indonesia are also outlined. Furthermore, visualization of concept relationships using VOSviewer software aids in identifying main themes and concept relationships in the literature. Thus, this study provides a comprehensive understanding of tax policy research in Indonesia, serving as a basis for further research and aiding policymakers in understanding key issues related to the tax system in the country.